Comparison of Eustachian tube ventilation function between cleft palate and normal patients using sonotubometry - Widodo, Dini Widiarni; Hisyam, Adila; Alviandi, Widayat; Mansyur, Muchtaruddin (JPRAS open, 2021)
To compare Eustachian tube ventilation function between cleft palate subjects and normal subjects using sonotubometry. A comparative cross-sectional study was conducted at the Department Otolaryngology-Head and Neck Surgery of Ciptomangunkusumo National Hospital, Universitas Indonesia, Jakarta, from June 2013 to January 2014.There were 31 subjects with cleft palate and 62 healthy subjects aged ≤18 years, and both groups were matched according to age. Each subject underwent ear, nose, and throat examination with Veau classification and sonotubometry, a new assembly test in Indonesia. The results of the sonotubogram (the number of Eustachian tube openings, amplitude enhancement in dB, and the duration of Eustachian tube opening in ms) were then analyzed with SPSS using chi-square and Mann–Whitney tests. Subjects with cleft palate had lower Eustachian tube function than healthy subjects using three sonotubometry parameters (p < 0.001). The proportion of Eustachian tube dysfunction based on the Veau classification was significant (p < 0.001). In multivariate analysis, several determinant factors of Eustachian tube dysfunction were found, such as adenoid hypertrophy (risk factor6.46), the number of Eustachian tube openings (risk factor 36.21), and higher Veau classification (risk factor 10.41). Sonotubometry could be used to assess parameters of Eustachian tube function. Subjects with cleft palate have a higher risk of having Eustachian tube dysfunction, as do subjects with adenoid hypertrophy.